PENGARUH BAURAN PEMASARAN (4P) TERHADAP KEPUTUSAN PEMBELIAN SAYURAN PAPRIKA (CAPSICUM ANNUM L) DI HYPERMART TERNATE - Saputri, Yuyun Ayu; Basuki, Natal; Fatmawati, Mila; Mahmud, Haris (Universitas Khairun, 2024)
Hypermart is the largest retail company that provides a complete range ofneeds and almost all products needed by consumers are available at hypermartranging from household needs to grocery needs including fruits and vegetables.This study aims to analyze and determine the marketing mix (4p) that influencesthepurchasedecisionofpaprikavegetablesatHypermartTernate.AndToanalyze and find out the elements of the marketing mix that most influence thedecision to purchase paprika vegetables at Hypermart Ternate. This study wasconducted on all visitors who decided to buy paprika vegetables at HypermartTernate by determining samples using accidental sampling techniques. The resultsshowedthatthemarketingmix(4P)consistingofproduct,price,place,andpromotion of the purchase decision of paprika vegetables at Hypermart Ternateinfluencedthepurchasedecision.Thesignificantvalueofeachvariableis,productwith a value of0.038, price 0.022, place 0.003 and promotion0.008whichmeansthatthemarketingmix(4P)hasasignificanteffectonthedecisionto purchase peppers at Hypermart Ternate. The marketing mix element that mostinfluences the decision to purchase paprika vegetables at Hypermart Ternate is aplace with a significant value of 0.008 which means that it has a significantinfluenceon the decisionto purchasepeppers atHypermart Ternate